# Common fixed points of generalized Meir-Keeler *α*-contractions

- Deepesh Kumar Patel
^{1}Email author, - Thabet Abdeljawad
^{2, 3}and - Dhananjay Gopal
^{1}

**2013**:260

https://doi.org/10.1186/1687-1812-2013-260

© Patel et al.; licensee Springer. 2013

**Received: **5 March 2013

**Accepted: **9 September 2013

**Published: **7 November 2013

## Abstract

Motivated by Abdeljawad (Fixed Point Theory Appl. 2013:19, 2013), we establish some common fixed point theorems for three and four self-mappings satisfying generalized Meir-Keeler *α*-contraction in metric spaces. As a consequence, the results of Rao and Rao (Indian J. Pure Appl. Math. 16(1):1249-1262, 1985), Jungck (Int. J. Math. Math. Sci. 9(4):771-779, 1986), and Abdeljawad itself are generalized, extended and improved. Sufficient examples are given to support our main results.

**MSC:**47H10, 54H25.

### Keywords

common fixed points Meir-Keeler contraction generalized Meir-Keeler*α*-contraction

*α*-admissible reciprocally continuous absorbing maps

## 1 Introduction and preliminaries

This contraction has further been generalized and studied by various authors (see [2–15]). Very recently, Abdeljawad [16] (see also [17]) established some fixed point results for *α*-contractive-type maps (due to Samet *et al.* [18]) to Meir-Keeler versions for single and a pair of maps. In this article, we prove some common fixed point theorems for three and four self-mappings satisfying generalized Meir-Keeler *α*-contractions. Thus, we provide an affirmative answer to the question of Abdeljawad (see [16], Remark 17).

Let us recall some definitions, which we will use in our main results.

*X*, and let $\alpha :X\times X\to [0,\mathrm{\infty})$ be a mapping, then the mapping

*f*is called

*α*-admissible if

*α*-admissible if

Let *f* and *g* ($f\ne g$) be two self-mappings defined on a metric space $(X,d)$, then *f* is called *g*-absorbing if there exists some real number $R>0$ such that $d(gx,gfx)\le Rd(fx,gx)$ for all *x* in *X*. Analogously, *g* will be called *f*-absorbing if there exists some real number $R>0$ such that $d(fx,fgx)\le Rd(fx,gx)$ for all *x* in *X*. The pair of self-maps $(f,g)$ will be called absorbing if it is both *g*-absorbing as well as *f*-absorbing. In particular, if we take *g* to be the identity map on *X*, then *f* is trivially *I*-absorbing. Similarly, *I* is also *f*-absorbing in respect to *f*.

**Definition 1.3** (*cf.* [21])

Two self-mappings *f* and *g* of a metric space $(X,d)$ are called reciprocally continuous if and only if $fg{x}_{n}\to ft$ and $gf{x}_{n}\to gt$ whenever $\{{x}_{n}\}$ is a sequence in *X* such that ${lim}_{n\to \mathrm{\infty}}f{x}_{n}={lim}_{n\to \mathrm{\infty}}g{x}_{n}=t$ for some $t\in X$.

## 2 Main results

We begin with the following definitions.

**Definition 2.1**Let $f,g,T:X\to X$ be three self-mappings of a non-empty set

*X*, and let $\alpha :T(X)\times T(X)\to [0,\mathrm{\infty})$ be a mapping, then the pair $(f,g)$ is called

*α*-admissible with respect to

*T*(in short, $(f,g)$ is ${\alpha}_{T}$-admissible) if for all $x,y\in X$,

**Definition 2.2**Let $f,g,S,T:X\to X$ be four self-mappings of a non-empty set

*X*, and let $\alpha :S(X)\cup T(X)\times S(X)\cup T(X)\to [0,\mathrm{\infty})$ be a mapping, then the pair $(f,g)$ is called

*α*-admissible with respect to

*S*and

*T*(in short, $(f,g)$ is ${\alpha}_{S,T}$-admissible) if for all $x,y\in X$,

Clearly, if $S=T=I$ (identity map), then the definitions above imply Definition 1.1.

In order to extend and improve the result contained in [16] for three self-mappings, we now introduce the concept of generalized Meir-Keeler ${\alpha}_{T}$-contractive mappings as follows.

**Definition 2.3**Let $(X,d)$ be a metric space, and $f,g,T:X\to X$ are self-mappings. Then we say that the pair $(f,g)$ is a generalized Meir-Keeler ${\alpha}_{T}$-contractive pair of type ${m}_{3}$ (${M}_{3}$, respectively) if given an $\u03f5>0$, there exists a $\delta >0$ such that

**Definition 2.4** Let *f*, *g*, and *T* be three self-mappings on a metric space $(X,d)$ such that $f(X)\cup g(X)\subseteq T(X)$. If for a point ${x}_{0}\in X$, there exists a sequence $\{{x}_{n}\}$ such that $T{x}_{2n+1}=f{x}_{2n}$, $T{x}_{2n+2}=g{x}_{2n+1}$, $n=0,1,2,\dots $ , then $\mathcal{O}(f,g,T,{x}_{0})=\{T{x}_{n}:n=1,2,\dots \}$ is called the orbit for $(f,g,T)$ at ${x}_{0}$. The space $(X,d)$ is called $(f,g,T)$-orbitally complete at ${x}_{0}$ iff every Cauchy sequence in $\mathcal{O}(f,g,T,{x}_{0})$ converges to a point in *X*. *X* is called $(f,g,T)$-orbitally complete if it is so at every $x\in X$.

Our first result is the following.

**Theorem 2.1**

*Let*$(X,d)$

*be an*$(f,g,T)$-

*orbitally complete metric space*.

*Suppose that*$(f,g)$

*is generalized Meir*-

*Keeler*${\alpha}_{T}$-

*contractive pair of type*${m}_{3}$

*and satisfies the following conditions*:

- (i)
$(f,g)$

*is*${\alpha}_{T}$-*admissible*; - (ii)
*there exists*${x}_{0}\in X$*such that*$\alpha (T{x}_{0},f{x}_{0})\ge 1$; - (iii)
*on the*$(f,g,T)$-*orbit of*${x}_{0}$,*we have*$\alpha (T{x}_{n},T{x}_{j})\ge 1$*for all**n**even and*$j>n$*odd*.

*Then*$\{T{x}_{n}\}$

*is a Cauchy sequence*.

*Moreover*,

*if*

- (iv)
$\alpha (T{x}_{n},T{x}_{n+1})\ge 1$

*for all**n*,*and*$T{x}_{n}\to x$*implies that*$\alpha (T{x}_{n},Tx)\ge 1$*for all**n*; - (v)
*one of the pairs*$(f,T)$*and*$(g,T)$*is absorbing as well as reciprocal continuous*.

*Then* *f*, *g*, *and* *T* *have a common fixed point*.

*Proof*Let ${x}_{0}\in X$ such that $\alpha (T{x}_{0},f{x}_{0})\ge 1$. Define the sequences $\{{x}_{n}\}$ and $\{T{x}_{n}\}$ in

*X*given by the rule

Now, to obtain a common fixed point of *f*, *g*, and *T*, we take the following steps.

Step 1: We show that there exists a point $z\in X$ such that $T{x}_{n}\to z$ as $n\to \mathrm{\infty}$. For this, first, we claim that $\{T{x}_{n}\}$ is a Cauchy sequence. Two cases arise: either $T{x}_{n}=T{x}_{n+1}$ for some *n* or $T{x}_{n}\ne T{x}_{n+1}$ for each *n*.

*n*. We first assume that

*n*is even,

*i.e.*, $T{x}_{2m}=T{x}_{2m+1}$ but $T{x}_{2m+1}\ne T{x}_{2m+2}$, then by (6),

which is a contradiction. Hence $T{x}_{2m+1}=T{x}_{2m+2}$. By proceeding in this way, we obtain $T{x}_{2m+k}=T{x}_{2m}$ for all $k\in \mathcal{N}$. Similar is the case when *n* is odd. Thus, we conclude that $\{T{x}_{n}\}$ is a Cauchy sequence.

*n*. Applying (6), we have

We now show that $\{T{x}_{n}\}$ is a Cauchy sequence.

*m*,

*n*with $m>n>N$, we have $d(T{x}_{m},T{x}_{n})\ge 2\u03f5$. Choose a number

*δ*, $0<\delta <\u03f5$ for which contractive condition (4) is satisfied. Since $d(T{x}_{n},T{x}_{n+1})\to 0$, there exists integer $N=N(\delta )$ such that $d(T{x}_{i},T{x}_{i+1})<\frac{\delta}{6}$ for all $i\ge N$. With this choice of

*N*, pick

*m*,

*n*with $m>n>N$ such that

*n*is even. Suppose that

which contradicts (11). Therefore, $\{T{x}_{n}\}$ is a Cauchy sequence. Since *X* is $(f,g,T)$-orbitally complete, so there exists a point $z\in X$ such that $T{x}_{n}\to z$ as $n\to \mathrm{\infty}$. Consequently, $f{x}_{2n}\to z$ and $g{x}_{2n+1}\to z$.

*z*is common fixed point of $(f,g,T)$. In view of assumption (v), without loss of generality, let the pair $(f,T)$ be absorbing and reciprocal continuous. Then the reciprocal continuity of

*f*and

*T*implies that

*T*is

*f*-absorbing, so there exists an $R>0$ such that

*f*is

*T*-absorbing, so we have

letting $n\to \mathrm{\infty}$, we get $Tf{x}_{2n}\to z$. By the uniqueness of the limit, we have $z=fz=Tz$.

Letting $n\to \mathrm{\infty}$, we get $d(z,gz)\le \frac{1}{2}d(z,gz)$, which implies that $z=gz$. Thus, *z* is a common fixed point of *f*, *g*, and *T*. This completes the proof of the theorem. □

By putting $f=g$ and $T=I$ (identity map) in Theorem 2.1, we get the following result as a corollary.

**Corollary 2.1**

*Let*$(X,d)$

*be an*

*f*-

*orbitally complete metric space*,

*where*

*f*

*is a self*-

*mapping on*

*X*.

*Also*,

*let*$\alpha :X\times X\to [0,\mathrm{\infty})$

*be a mapping*.

*Assume the following*:

- (i)
*f**is**α*-*admissible*; - (ii)
*there exists an*${x}_{0}\in X$*such that*$\alpha ({x}_{0},f{x}_{0})\ge 1$; - (iii)
*for given*$\u03f5>0$,*there exists a*$\delta >0$*such that*$\begin{array}{r}\u03f5\le {m}_{1}(x,y)<\u03f5+\delta \phantom{\rule{1em}{0ex}}\u27f9\phantom{\rule{1em}{0ex}}\alpha (x,y)d(fx,fy)<\u03f5,\\ \mathit{\text{where}}{m}_{1}(x,y)=max\{d(x,y),\frac{1}{2}[d(x,fx)+d(y,fy)],\frac{1}{2}[d(x,fy)+d(y,fx)]\};\end{array}$ - (iv)
*on the**f*-*orbit of*${x}_{0}$,*we have*$\alpha ({x}_{n},{x}_{j})\ge 1$*for all**n**even and*$j>n$*odd*.

*Then*, *f* *has a fixed point in the* *f*-*orbit* $\{{x}_{n}\}$ *of* ${x}_{0}$, *or* *f* *has a fixed point* *z* *and* ${lim}_{n\to \mathrm{\infty}}{x}_{n}=z$.

**Example 2.1**Let $X=[0,2]$ be endowed with the standard metric $d(x,y)=|x-y|$ for all $x,y\in X$. Define $f:X\to X$ by

*f*is not a Meir-Keeler contraction. To see this consider $\u03f5=\frac{1}{2}$, $x=\frac{1}{4}$, and $y=\frac{3}{4}$, then for any $\delta >0$, we have $\u03f5\le {m}_{1}(x,y)<\u03f5+\delta $, but $d(fx,fy)=d(0,\frac{3}{2})=\frac{3}{2}>\u03f5$. However,

*f*is a generalized Meir-Keeler

*α*-contraction, where $\alpha :X\times X\to [0,\mathrm{\infty})$ is defined by

Clearly, *f* has two fixed points, namely $x=0$ and $x=\frac{3}{2}$. Notice that $\alpha (\frac{3}{2},0)=0<1$.

*α*-contractive mapping, we will consider the following hypothesis.

- (H)
For all fixed points

*x*and*y*of $(f,g,T)$, we have $\alpha (Tx,Ty)\ge 1$.

**Theorem 2.2** *Adding condition* (H) *to the hypotheses of Theorem* 2.1 (*resp*., *Corollary* 2.1), *we obtain the uniqueness of the common fixed point of* *f*, *g*, *and* *T*.

*Proof*Let

*z*be the common fixed point obtained as $T{x}_{n}\to z$ and

*u*is another common fixed point. Then, (6) and condition (H) yield to

Thus, we reach $d(z,u)<d(z,u)$, and hence $z=u$. □

The following example illustrates Theorem 2.2.

**Example 2.2**Let $X=[2,20]$ and

*d*be the usual metric on

*X*. Define $f,g,T:X\to X$ as follows:

*f*,

*g*, and

*T*do not satisfy the general Meir-Keeler contractive condition. To see this, consider $\u03f5=\frac{3}{4}$, $x=3$ and $y\in [2,3)$, then for any $\delta >0$, we have $\u03f5\le m(x,y)<\u03f5+\delta $, but $d(fx,gy)=d(3,2)=1>\u03f5$. However,

*f*,

*g*, and

*T*satisfy the generalized Meir-Keeler

*α*-contractive condition (4) with the mapping $\alpha :T(X)\times T(X)\to [0,\mathrm{\infty})$ defined by

Also, all the hypotheses of Theorem 2.1 with condition (H) are satisfied, and clearly $x=3$ is our unique common fixed point. Indeed, hypothesis (ii) is satisfied with ${x}_{0}=3$, and here $T{x}_{n}=3$ is a sequence, for which hypotheses (iii) and (iv) are satisfied. Also in view of the sequence ${x}_{n}=3$, here both pairs $(f,T)$ and $(g,T)$ are reciprocal continuous as well as absorbing. Notice that $x=3$ is the point of discontinuity of the mappings *g* and *T*.

**Theorem 2.3**

*The conclusion of Theorem*2.1

*remains true if the assumption*(v)

*of Theorem*2.1

*is replaced by one of the following conditions*:

- (a)
$d(gx,Ty)\le max\{d(y,gx),d(y,Tx)\}$

*for all*$x,y\in X$*with right*-*hand side positive*. - (b)
$d(fx,Ty)\le max\{d(y,Tx),d(y,fx)\}$

*for all*$x,y\in X$*with right*-*hand side positive*.

*Proof* In view of Theorem 2.1, we have that $\{T{x}_{n}\}$ is a Cauchy sequence, and $T{x}_{n}\to z\in X$ as $n\to \mathrm{\infty}$, and, consequently, $f{x}_{2n}$ and $g{x}_{2n+1}$ also converge to *z* as $n\to \mathrm{\infty}$.

Clearly, $T{x}_{n}\ne z$ for infinitely many *n*. We can as well assume that $T{x}_{n}\ne z$ for all *n*.

Letting $n\to \mathrm{\infty}$, we get $d(z,Tz)\le 0$, *i.e.,* $Tz=z$. If (b) holds, then also $Tz=z$.

letting $n\to \mathrm{\infty}$, we get $d(z,gz)\le \frac{1}{2}d(z,gz)$, which implies that $z=gz$.

letting $n\to \mathrm{\infty}$, we get $d(fz,z)\le \frac{1}{2}d(z,fz)$, which implies that $fz=z$. Thus, *z* is the common fixed point of *f*, *g*, and *T*. □

The following example demonstrates Theorem 2.3.

**Example 2.3**Let $X=[0,1]$ and

*d*be the usual metric on

*X*. Define $f,g,T:X\to X$ as follows:

*f*,

*g*, and

*T*satisfy all the conditions of Theorem 2.3 with the mapping $\alpha :T(X)\times T(X)\to [0,\mathrm{\infty})$ defined by

Clearly, none of the pairs $(f,T)$ and $(g,T)$ are reciprocal continuous. To see this consider the sequence ${x}_{n}=\frac{1}{2}+\frac{1}{n}$, then ${lim}_{n\to \mathrm{\infty}}f{x}_{n}={lim}_{n\to \mathrm{\infty}}T{x}_{n}=\frac{1}{4}$, but ${lim}_{n\to \mathrm{\infty}}fT{x}_{n}={lim}_{n\to \mathrm{\infty}}f(\frac{1}{4}+\frac{1}{2n})=\frac{1}{20}\ne 0=f(\frac{1}{4})$. Therefore, $(f,T)$ is not reciprocal continuous. To see that $(g,T)$ is not reciprocal continuous, one can consider the sequence ${y}_{n}=\frac{1}{4}+\frac{1}{n}$. Here, the involved mappings satisfy condition (a) of Theorem 2.3, and they have the unique common fixed $x=0$.

**Remark 2.1** Theorem 2.3 generalizes and extends Theorem 1.2 of Rao and Rao [22].

**Theorem 2.4** *Theorem* 2.1 *remains true if we replace* ${m}_{3}(x,y)$ *by* ${M}_{3}(x,y)$ *and condition* (iv) *by the following* (iv′):

(iv′) $\alpha (T{x}_{n},T{x}_{n+1})\ge 1$ *for all* *n* *and* $T{x}_{n}\to x$ *implies that* $\alpha (T{x}_{n},Tx)\ge K$ *for all* *n*, *where* $K>1$.

*Proof*The proof of $z=fz=Tz$ follows from Theorem 2.1. Now, suppose that $z\ne gz$, then by the help of condition (iv’), we have

By letting $n\to \mathrm{\infty}$, we conclude that $d(z,gz)\le {K}^{-1}d(z,gz)<d(z,gz)$, and hence $z=gz$. Thus, *z* is a common fixed point of *f*, *g*, and *T*. □

Example 2.2 above also satisfies Theorem 2.4.

**Remark 2.2** Theorem 2.4 generalizes and extends Theorem 1.3 of Rao and Rao [22].

By taking $T=I$ (identity map) in Theorem 2.4, we derive the following result as a corollary.

**Corollary 2.2**

*Let*$(X,d)$

*be an*$(f,g)$-

*orbitally complete metric space*,

*where*

*f*,

*g*

*are self*-

*mappings of*

*X*.

*Also*,

*let*$\alpha :X\times X\to [0,\mathrm{\infty})$

*be a mapping*.

*Assume the following*:

- (i)
$(f,g)$

*is**α*-*admissible*,*and there exists an*${x}_{0}\in X$*such that*$\alpha ({x}_{0},f{x}_{0})\ge 1$; - (ii)
*for given*$\u03f5>0$,*there exists a*$\delta >0$*such that*$\u03f5\le M(x,y)<\u03f5+\delta \phantom{\rule{1em}{0ex}}\mathit{\text{implies that}}\phantom{\rule{1em}{0ex}}\alpha (x,y)d(fx,gy)<\u03f5,$

*where*

- (iii)
*on the*$(f,g)$-*orbit of*${x}_{0}$,*we have*$\alpha ({x}_{n},{x}_{j})\ge 1$*for all**n**even and*$j>n$*odd*; - (iv)
$\alpha ({x}_{n},{x}_{n+1})\ge 1$

*for**n*,*and*${x}_{n}\to x$*implies that*$\alpha ({x}_{n},x)\ge K$*for all**n*,*where*$K>1$.

*Then*, *the pair* $(f,g)$ *has a common fixed point provided it is absorbing as well as reciprocal continuous*.

**Remark 2.3** Corollary 2.2 improves Theorem 8 contained in [16].

The next result is a common fixed point theorem for four self-mappings.

**Theorem 2.5**

*Let*

*f*,

*g*,

*S*,

*and*

*T*

*be four self*-

*mappings on a complete metric space*$(X,d)$

*such that*$f(X)\subseteq T(X)$

*and*$g(X)\subseteq S(X)$,

*and they satisfy the following conditions*:

- (i)
*the pair*$(f,g)$*is*${\alpha}_{S,T}$-*admissible*; - (ii)
*there exists a point*${x}_{0}\in X$*such that*$\alpha (S{x}_{0},f{x}_{0})\ge 1$; - (iii)
*for given*$\u03f5>0$,*there exists a*$\delta >0$*such that*$\u03f5\le {m}_{4}(x,y)<\u03f5+\delta \phantom{\rule{1em}{0ex}}\u27f9\phantom{\rule{1em}{0ex}}\alpha (Sx,Ty)d(fx,gy)<\u03f5,$(12)

*where*

- (iv)
*there exists a sequence*$\{{x}_{n}\}$*in**X**such that*$\alpha (S{x}_{n},T{x}_{j})\ge 1$*for all**n**even and*$j>n$*odd*;

*Then* *f*, *g*, *S*, *and* *T* *have a common fixed point provided both the pair* $(f,S)$ *and* $(g,T)$ *are absorbing as well as reciprocal continuous*.

*Proof*Let ${x}_{0}\in X$ such that $\alpha (S{x}_{0},f{x}_{0})\ge 1$. Define sequences $\{{x}_{n}\}$ and $\{{y}_{n}\}$ in

*X*as

This can be done since $f(X)\subseteq T(X)$ and $g(X)\subseteq S(X)$.

that is, $\alpha (S{x}_{n+1},T{x}_{n+2})\ge 1$, when *n* is odd and $\alpha (T{x}_{n+1},S{x}_{n+2})\ge 1$ when *n* is even.

Now, we claim that $\{{y}_{n}\}$ is a Cauchy sequence.

*n*. We first assume that

*n*is odd,

*i.e.*, ${y}_{2m+1}={y}_{2m+2}$ and suppose that ${y}_{2m+2}\ne {y}_{2m+3}$, then by applying (13) and (14), we get

a contradiction. Hence ${y}_{2m+2}={y}_{2m+3}$. By proceeding in this manner, we obtain ${y}_{2m+k}={y}_{2m+1}$ for all $k\ge 1$. Similarly, when we assume *n* as even, then we obtain ${y}_{2m+k}={y}_{2m}$ for all $k\ge 1$, and so $\{{y}_{n}\}$ is a Cauchy sequence.

*n*. Applying (13) and (14), we get

*N*such that for each $n\ge N$, we have

*N*, there exist integers $m>n>N$ such that $d({y}_{m},{y}_{n})\ge 2\u03f5$. Choose a number

*δ*, $0<\delta <\u03f5$, for which contractive condition (12) is satisfied. By virtue of (16), there exists an integer

*N*such that $d({y}_{i},{y}_{i+1})<\frac{\delta}{6}$ for all $i\ge N$. With this choice of

*N*, pick integers $m>n>N$ such that

in which it is clear that $m-n>6$. Also from (17), it follows that $d({y}_{m},{y}_{n+1})>\u03f5+\frac{\delta}{3}$.

*n*is even. From (17), there exists the smallest odd integer $j>n$ such that

*i.e.*, $d({y}_{n+1},{y}_{j+1})<\u03f5$. But then

which contradicts (19). Therefore, $\{{y}_{n}\}$ is a Cauchy sequence. By the completeness of *X*, there exists a $z\in X$ such that ${y}_{n}\to z$ as $n\to \mathrm{\infty}$ and, consequentially, $f{x}_{2n}$, $T{x}_{2n+1}$, $g{x}_{2n+1}$ and $S{x}_{2n+2}\to z$ as $n\to \mathrm{\infty}$.

Since the pair $(f,S)$ is reciprocal continuous and absorbing, so by reciprocal continuity, we have $fS{x}_{2n}\to fz$ and $Sf{x}_{2n}\to Sz$ as $n\to \mathrm{\infty}$. By absorbing property, there is an $R>0$ such that $d(f{x}_{2n},fS{x}_{2n})\le Rd(f{x}_{2n},S{x}_{2n})$ and $d(S{x}_{2n},Sf{x}_{2n})\le Rd(f{x}_{2n},S{x}_{2n})$, which letting $n\to \mathrm{\infty}$ gives $fS{x}_{2n}\to z$ and $Sf{x}_{2n}\to z$. Thus, we have $z=fz=Sz$. Similarly, the absorbing and reciprocal continuity of the pair $(g,T)$ provides us $z=gz=Tz$. Thus, *z* is a common fixed point of *f*, *g*, *S*, and *T*. □

**Theorem 2.6** *Adding the condition* (H-2): *For all common fixed points* *x* *and* *y* *of* *f*, *g*, *S*, *and* *T*, $\alpha (Sx,Ty)\ge 1$, *to the hypotheses of Theorem* 2.5, *the uniqueness of the fixed point is obtained*.

**Remark 2.4** Theorem 2.6 generalizes, extends and improves the results of Jungck (Theorem 3.1, [8]), Cho *et al.* (Theorem 3.2, [4]) and Rao and Rao [22].

## Declarations

### Acknowledgements

The authors would like to express their thanks to Prof. M. A Khamsi and the referees for their helpful comments and suggestions. The first author is thankful to S. V. National Institute of Technology, Surat, India for awarding Senior Research Fellow. The third author gratefully acknowledges the support from the CSIR, Govt. of India, Grant No.-25(0215)/13/EMR-II.

## Authors’ Affiliations

## References

- Meir A, Keeler E: A theorem on contraction mappings.
*J. Math. Anal. Appl.*1969, 28: 326–329. 10.1016/0022-247X(69)90031-6MathSciNetView ArticleMATHGoogle Scholar - Aydi H, Karapinar E: A Meir-Keeler common type fixed point theorem on partial metric space.
*Fixed Point Theory Appl.*2012., 2012: Article ID 26Google Scholar - Aydi H, Karapinar E: New Meir-Keeler-type tripled fixed point theorems on ordered partial metric space.
*Math. Probl. Eng.*2012., 2012: Article ID 409872Google Scholar - Cho YJ, Murthy PP, Jungck G: A common fixed point theorem of Meir and Keeler type.
*Int. J. Math. Math. Sci.*1993, 16(4):669–674. 10.1155/S0161171293000833MathSciNetView ArticleMATHGoogle Scholar - Cho YJ, Murthy PP, Jungck G: A theorem of Meir-Keeler type revisited.
*Int. J. Math. Math. Sci.*2000, 23(7):507–511. 10.1155/S0161171200002258MathSciNetView ArticleMATHGoogle Scholar - Bisht RK: Common fixed points of generalized Meir-Keeler type condition and nonexpansive mappings.
*Int. J. Math. Math. Sci.*2012., 2012: Article ID 786814Google Scholar - Jachymski J: Equivalent conditions and the Meir-Keeler-type theorems.
*J. Math. Anal. Appl.*1995, 194: 293–303. 10.1006/jmaa.1995.1299MathSciNetView ArticleMATHGoogle Scholar - Jungck G: Compatible mappings and common fixed points.
*Int. J. Math. Math. Sci.*1986, 9(4):771–779. 10.1155/S0161171286000935MathSciNetView ArticleMATHGoogle Scholar - Jungck G, Moon KB, Park S, Rhoades BE: On generalizations of the Meir-Keeler-type contractive maps: corrections.
*J. Math. Anal. Appl.*1993, 180: 221–222. 10.1006/jmaa.1993.1397MathSciNetView ArticleMATHGoogle Scholar - Jungck G, Pathak HK: Fixed points via ‘biased maps’.
*Proc. Am. Math. Soc.*1995, 123(7):2049–2060.MathSciNetMATHGoogle Scholar - Maiti M, Pal TK: Generalizations on two fixed point theorems.
*Bull. Calcutta Math. Soc.*1978, 70(2):57–61.MathSciNetMATHGoogle Scholar - Pant RP, Joshi PC, Gupta V: A Meir-Keeler-type fixed point theorem.
*Indian J. Pure Appl. Math.*2001, 32(6):779–787.MathSciNetMATHGoogle Scholar - Pant RP, Lohani AB, Jha K: Meir-Keeler-type fixed point theorem and reciprocal continuity.
*Bull. Calcutta Math. Soc.*2002, 94(6):459–466.MathSciNetMATHGoogle Scholar - Park S, Rhoades BE: Meir-Keeler-type contractive condition.
*Math. Jpn.*1981, 26(1):13–20.MathSciNetMATHGoogle Scholar - Rhoades BE, Park S, Moon KB: On generalizations of the Meir-Keeler type contraction maps.
*J. Math. Anal. Appl.*1990, 146: 482–494. 10.1016/0022-247X(90)90318-AMathSciNetView ArticleMATHGoogle Scholar - Abdeljawad T: Meir-Keeler
*α*-contractive fixed and common fixed point theorems.*Fixed Point Theory Appl.*2013., 2013: Article ID 19Google Scholar - Abdeljawad T, Gopal D: Erratum to ‘Meir-Keeler
*α*-contractive fixed and common fixed point theorems’.*Fixed Point Theory Appl.*2013., 2013: Article ID 110Google Scholar - Samet B, Vetro C, Verto P: Fixed point theorems for
*α*-*ψ*-contractive type mappings.*Nonlinear Anal.*2012, 75: 2154–2165. 10.1016/j.na.2011.10.014MathSciNetView ArticleMATHGoogle Scholar - Gopal D, Pant RP, Ranadive AS: Common fixed point of absorbing maps.
*Bull. Marathwada Math. Soc.*2008, 9(1):43–48.Google Scholar - Gopal D, Imdad M, Hasan M, Patel DK: Proving common fixed point theorems for Lipschitz-type mappings via absorbing pair.
*Bull. Math. Anal. Appl.*2011, 3(4):92–100.MathSciNetMATHGoogle Scholar - Pant RP: Common fixed points of four mappings.
*Bull. Calcutta Math. Soc.*1998, 90(4):281–286.MathSciNetMATHGoogle Scholar - Rao JHN, Rao KPR: Generalizations of fixed point theorems of Meir and Keeler type.
*Indian J. Pure Appl. Math.*1985, 16(1):1249–1262.MathSciNetMATHGoogle Scholar

## Copyright

This article is published under license to BioMed Central Ltd. This is an open access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/2.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.